2013
DOI: 10.1016/j.ijsu.2013.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node ratio is a stronger prognotic factor than microsatellite instability in colorectal cancer patients: Results from a 7 years follow-up study

Abstract: According to our results the MSI-H status was associated with particular features (right locations/locally advanced tumors). The results of a long-term follow-up indicate a trend for better survival in MSI-H vs MSS patients. Notably, an increased LNR is associated with worse survivals, both at the univariate and multivariate analysis, displaying this ratio as the strongest prognostic factor of cancer-related survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Despite better outcomes, our study showed a positive correlation between MSI status and poor differentiation, which is reported as a factor of poor prognosis. This result is in agreement with several reports [2123].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Despite better outcomes, our study showed a positive correlation between MSI status and poor differentiation, which is reported as a factor of poor prognosis. This result is in agreement with several reports [2123].…”
Section: Discussionsupporting
confidence: 94%
“…The prognosis value of MSI tumors could be explained by the low rate of metastasis at diagnosis observed in these tumors, which is confirmed in our study. Indeed, Ferri et al [21] have reported that the MSI patients with locally advanced colorectal cancers had a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…If MSI status is associated with the total number of harvested LNs, we can consider the possibility of a relationship between MSI status and LNR. Ferri et al [ 33 ] reported no association between MSI status and LNR. Contrary to the previous study, this study found a significant relationship of MSI-H with low LNR in both all stage and stage III.…”
Section: Discussionmentioning
confidence: 99%
“…A major issue is establishment of an appropriate cut‐off point to divide the LNR into a categorical variable. Methods described to determine this include receiver operating characteristic (ROC) curves, Martingale residuals and the use of statistical software such as X‐tile or simply dividing the group into quartiles . There is wide variability between studies in the cut‐off point used.…”
Section: Introductionmentioning
confidence: 99%